Coupling coefficients of the disk dielectric microresonators with whispering gallery modes - A. A. Trubin (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2015)
Calculation results of the Disk dielectric microresonators coupling coefficients are presented. Microresonator coupling coefficients as a functions of main parameters is considered. S-matrix frequency dependences of both bandstop and bandpass filters on Disk microresonators of infrared wavelength range is calculated.